Implementation Of Innovation Disdukcapil In The Pontianak Civil Registration Services Pandemic During Covid-19 - Ira Patriani (Cita Konsultindo Research Center, 2023)
This study discusses the City's innovation in providing public services during the Covid 19 Outbreak. This study uses a qualitative method with literature and an empirical approach. Data is obtained by analyzing laws, written regulations, and social phenomena in society. Apart from doing fact testing in the field as a des sein to the lockdown policy as an applicable guideline or das sollen. The data analysis method used in this paper is a qualitative data analysis method. The analyzed data will then be presented in systematic writing. The results in this study Pontianak City in implementing the innovation of population administration services at the Population and Civil Registration Office of Pontianak City, there is an innovation, namely the innovation of taking online queue numbers and online services by trying to reduce or even try to eliminate manual or conventional services.